2007
DOI: 10.1534/genetics.107.074286
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Transcriptomic Changes Associated With Potato Autopolyploidization

Abstract: Polyploidy is remarkably common in the plant kingdom and polyploidization is a major driving force for plant genome evolution. Polyploids may contain genomes from different parental species (allopolyploidy) or include multiple sets of the same genome (autopolyploidy). Genetic and epigenetic changes associated with allopolyploidization have been a major research subject in recent years. However, we know little about the genetic impact imposed by autopolyploidization. We developed a synthetic autopolyploid serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
167
0
11

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(191 citation statements)
references
References 68 publications
13
167
0
11
Order By: Relevance
“…The results suggest that artificial genome doubling of diploid apple genotypes decreased plant vigour. Although polyploidization in plants is often associated with increased vigour, e.g., triploid apples (Sedysheva, Gorbacheva 2013) and hexaploid Hibiscus (Van Laere et al 2006, artificial genome doubling is very frequently associated with a decreased growth rate, e.g., in Citrus (Allario et al 2011;Guerra et al 2014), Spathiphyllum (Van Laere et al 2011, Platanus (Liu et al (Stupar et al 2007), and tetraploid Zea mays (Riddle et al 2006). Several observations show the increased vigour of triploid apple cultivars (Sedysheva, Gorbacheva 2013) and triploid Zea mays (Riddle et al 2006) over diploids but decreased vigour of higher ploidy levels and own observations of an increased vigour in tetraploid azalea; however, decreased vigour of hexaploids compared to diploids (Eeckhaut et al 2006) suggests that plant species potentially possess an optimal ploidy degree, below or above which its growth will be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that artificial genome doubling of diploid apple genotypes decreased plant vigour. Although polyploidization in plants is often associated with increased vigour, e.g., triploid apples (Sedysheva, Gorbacheva 2013) and hexaploid Hibiscus (Van Laere et al 2006, artificial genome doubling is very frequently associated with a decreased growth rate, e.g., in Citrus (Allario et al 2011;Guerra et al 2014), Spathiphyllum (Van Laere et al 2011, Platanus (Liu et al (Stupar et al 2007), and tetraploid Zea mays (Riddle et al 2006). Several observations show the increased vigour of triploid apple cultivars (Sedysheva, Gorbacheva 2013) and triploid Zea mays (Riddle et al 2006) over diploids but decreased vigour of higher ploidy levels and own observations of an increased vigour in tetraploid azalea; however, decreased vigour of hexaploids compared to diploids (Eeckhaut et al 2006) suggests that plant species potentially possess an optimal ploidy degree, below or above which its growth will be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In general, polyploid plants often possess larger cell sizes and sometimes larger biomass, height and girth (Comai 2005;Oselebe et al 2006), leaf size and thickness (Stupar et al 2007), fruit mass (Oselebe et al 2006;Vandenholt et al 1995), and stomata size (Miller et al 2012;Mishra 1997;Speckmann et al 1965). The phenotypic alterations sometimes affect secondary metabolites (Cohen et al 2013;Dhawan and Lavania 1996).…”
mentioning
confidence: 99%
“…Laticifer and parenchyma diameters and epidermis size were almost the same size for tetraploids and diploids (Table 2, Figure 2). For many plant polyploids, scores for individual leaf areas or leaf thicknesses are higher than those of the normal diploid plants due to a larger increment of cell size (Miller et al 2012;Oselebe et al 2006;Stupar et al 2007), but the tendency toward increased cell size in E. ulmoides was less than that of other plant species.…”
mentioning
confidence: 99%
“…The autooctoploid switchgrass lines could be used as a model to illustrate the consequences of polyploidy on the genome and gene expression levels in switchgrass [51]. In this case, the pairs of tetraploid and autooctoploid lines derived from the same SE callus lines, with similar or close genetic backgrounds, could be used to identify genes that are differently regulated by chromosome doubling through expression profiling [54][55][56]. It was also recently reported that switchgrass SE callus could be generated from in vitro culture of inflorescences [57].…”
Section: Discussionmentioning
confidence: 99%